Strong electron-phonon coupling and predicted high superconducting transition temperature of MXenesrevealed in 2H-Mo2N under biaxial stress - Komsilp Kotmool; Prutthipong Tsuppayakorn-aek; Thiti Bovornratanaraks; Thanayut Kaewmaraya; Rachsak Sakdanuphab; Aparporn Sakulkalavek; Rajeev Ahuja; Wei Luo (My University, 2023)
Abstract Superconducting Mo-based MXenes have been intensively investigated due to their superior Tc values compared with other MXenes. This work reports the unexpectedly strong electron-phonon coupling (EPC) and the highest Tc record (≈ 38 K) among the MXenes revealed in the 2H-Mo2N under biaxial stress. At first, its excellent mechanical properties are demonstrated with an ideal strength of 37 GPa and elastic modulus of 438 GPa. We found that the nature of covalent bonding between the Natoms contributes to the extraordinary stiffness and elasticity of 2H-Mo2N compared with the 1T counterpart. Subsequently, EPC and corresponding Tc are elucidated upon the dynamically stable strain range. For strain-free 2H-Mo2N, the EPC constant(λ) and Tc are 1.3 and 22.7 K, respectively. This Tc is significantly higher than those of 2H-Mo2C (4.3 K), 1T-Mo2N (16.8 K), and other pristine MXenes. The material exhibits substantial improvement in λ and Tc when subjected to compressive and tensile stresses. The obvious strong EPC with λ over 2.0 occurs at strains of -4%, -2.5%, and 5%, yielding Tc’s of 37.8, 35.4, and 28.9 K, respectively. Our findings suggest that the strain-dependent feature and energy levels of electronic bands play an essential role in enhancing EPC. Moreover, the stronger EPC in Mo2N compared with Mo2C is clarified based on lattice vibrations. Therefore, this work paves a practical approach for designing 2D superconducting materials using tuning atomic recipes and strain-dependent engineering.
Keywords: MXenes; Strain (injury); Lattice constant; MAX phases; MXene and MAX Phase Materials